2014
DOI: 10.1063/1.4896279
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trench defects in InGaN/GaN light emitting diodes and implications for the “green gap” problem

Abstract: The impact of trench defects in blue InGaN/GaN light emitting diodes (LEDs) has been investigated. Two mechanisms responsible for the structural degradation of the multiple quantum well (MQW) active region were identified. It was found that during the growth of the p-type GaN capping layer, loss of part of the active region enclosed within a trench defect occurred, affecting the top-most QWs in the MQW stack. Indium platelets and voids were also found to form preferentially at the bottom of the MQW stack. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…So far, inhomogeneous indium distribution, dislocations, and surfacerelated defects have been reported. [11][12][13][14] Cation vacancies have been predicted to play a crucial role in Shockley-ReadHall recombination in wide-band-gap semiconductors. 15 Experimental studies of vacancy-type defects in thin-film III-nitrides have been extensively performed by positron annihilation spectroscopy (see Refs.…”
Section: à3mentioning
confidence: 99%
“…So far, inhomogeneous indium distribution, dislocations, and surfacerelated defects have been reported. [11][12][13][14] Cation vacancies have been predicted to play a crucial role in Shockley-ReadHall recombination in wide-band-gap semiconductors. 15 Experimental studies of vacancy-type defects in thin-film III-nitrides have been extensively performed by positron annihilation spectroscopy (see Refs.…”
Section: à3mentioning
confidence: 99%
“…It has been suggested that defect formation may occur as a consequence of either the higher In content or lower QW growth temperature, which may act as a contributory factor to the "green gap." 10 In particular, it has been shown that the use of low growth temperatures can lead to an increased density of structural defects 11 and impurity incorporation in GaN 12 and InGaN. 13 There is also a growing body of evidence that point defects are introduced into InGaN layers as the indium composition is increased.…”
mentioning
confidence: 99%
“…However, beyond 520 nm, toward a true-green wavelength of 555 nm, high lattice-and thermal-mismatch cause the nucleation of threading dislocations in materials with a drastic reduction in internal quantum efficiency, which constitutes the efficiency roll-over and "green gap" in solid-state lighting. 1 An investigation into alternative materials technology reveals that high photoluminescence quantum efficiency (PLQE) of approximately 70% has been demonstrated in solutionprocessed organic-inorganic hybrid perovskite semiconductors. 2 Previous studies have successfully identified materials for light emitters in the form of vertical microcavities, 2,3 whispering gallery cavities, 4 spherical resonators, 5 and free cavity.…”
mentioning
confidence: 99%